First Trimester Spontaneous Uterine Rupture in a Young Woman with Uterine Anomaly - Esra Nur Tola (Hindawi Limited, 2014)
Spontaneous uterine rupture is a life-threatening obstetrical emergency carrying a high risk for the mother and the fetus. Spontaneous uterine rupture in early pregnancy is very rare complication and it occurs usually in scarred uterus. Uterine anomalies are one of the reasons for spontaneous unscarred uterine rupture in early pregnancy. Obstetricians must consider this diagnosis when a pregnant patient presented with acute abdomen in early pregnancy. We present a case of spontaneous uterine rupture at 12 weeks of gestation in 24-year-old multigravida who had uterine anomaly presenting as an acute abdomen. Our preoperative diagnosis was ectopic pregnancy. Emergency laparotomy confirmed a spontaneous uterine rupture. Uterine anomaly is a risk factor for spontaneous uterine rupture in the early pregnancy. Clinical signs of uterine rupture in early pregnancy are nonspecific and must be distinguished from acute abdominal emergencies.